Incidência de infecção hospitalar em portadores do HIV: estudo comparativo com pacientes não-HIV - SARAIVA, Danielle de Lima (Universidade Federal do Pará, 2017)
HIV/AIDS patients may be exposed to the same risks for acquisition of nosocomial infections than non-HIV/AIDS patients, however, factors related to the immune suppression of former patients represent important paper in the pathogenesis for the development of nosocomial infections. This study investigated and compared the incidence of infections between HIV infected inpatients and non-infected inpatients in the Infectious Diseases Service of Hospital Universitário João de Barros Barreto. Nosocomial infections were related to invasive procedures (mechanical ventilation, urinary and central vascular catheter). It was an analytical, observational and prospective study, accomplished from February to December, 2007. Daily visits were performed by infection control team and the researcher from the first day in the Hospital to his discharge. There were reported 1.130 exits and 20.276 patients-day; 40 patients developed nosocomial infections and 17 (42,5%) non-HIV patients had 19 (39,6%) infections and 23 (57,5%) HIV patients developed 29 (60,4%) infections; eleven (55%) of these 23 patients had T4 cells counts less than 100cells/mm3 and 15 (65,22%) deaths were related to nosocomial infections. Hospital infections rates in HIV patients were higher than in non-HIV patients (3.09 versus 1.74 infections by 1000 patients-day). Pneumonia was the most frequent infection site an its incidence was 1,6 episodes for 1000 patients-day. Urinary tract infection in non-HIV patients was 12,11 episodes by 1000 urinary catheters-day compared to 4,41 episodes by 1000 urinary catheters-day in HIV positive patients. In conclusion, HIV patients are more susceptible to acquire nosocomial infections probably because of immune suppression related to HIV infection and invasive procedures and preventive and control measures should be directed to this patient population.